Understanding Students’ Experiences in Their Own Words: Moving Beyond a Basic Analysis of Student Engagement - Wong, Arch (Canadian Journal of Higher Education, 2015)
This study examines the lived experiences of students as expressed in their reflections on their experiences of learning at Ambrose University in Calgary. It uses quantitative outcomes-related data from the National Survey of Student Engagement and the Theological School Survey of Student Engagement to illuminate qualitative data obtained through student focus groups. The analysis of the qualitative data was conducted using the constant comparative method developed by Glaser and Strauss. The study concludes with recommendations for improving student engagement.